Recursion Example Three
Defining Rule

t1 = 1

t2 = 1

tn = tn-2 + tn-1


Generating the Sequence

Knowing that the first term is one and the second term is one (t1 = 1 and t2 = 1), calculate the value of the third term (t3)

Since we need to calculate t3, substitute n = 3 into the third part of the recursive rule (tn = tn-2 + tn-1)


      t(3) = t(3)-2 + t(3)-1

      t3 = t1 + t2                  (But it is known that t1 = 1 and t2 = 1)

      t3 = 1 + 1

      t3 = 2


Repeat this process to find t4.

Knowing that the first three terms are one, one and two (t1 = 1, t2 = 1 and t3 = 2) calculate the value of the fourth term (t4)

Since we need to calculate t4, substitute n = 4 into the third part of the recursive rule (tn = tn-2 + tn-1)


      t(4) = t(4)-2 + t(4)-1

      t4 = t2 + t3                  (But it is known that t2 = 1 and it was calculated that t3 = 2)

      t4 = 1 + 2

      t4 = 3


Repeat this process to find t5.

Knowing that the first four terms are one, one, two and three (t1 = 1, t2 = 1, t3 = 2 and t4 = 3) calculate the value of the fifth term (t5)

Since we need to calculate t5, substitute n = 5 into the third part of the recursive rule (tn = tn-2 + tn-1)


      t(5) = t(5)-2 + t(5)-1

      t5 = t3 + t4                  (But it was calculated that t3 = 2 and t4 = 3)

      t5 = 2 + 3

      t5 = 5


Repeat this process to find as many terms as required.


Sequence: 1, 1, 2, 3, 5, 8, 13, 21, 34, 55, 89, 144, . . .

Sequence: Starting with one and one, add two succesive terms of the sequence to determine the next term of the sequence.